Przepływ krwi i parametry morfologiczne tarczy nerwu wzrokowego u pacjentów z jaskrą niskociśnieniową i jaskrą pierwotną otwartego kąta oraz u osób zdrowych - Gronkowska, Jolanta; Karczewicz, Danuta (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
The aim of the present study was to compare selected morphological parameters of the optic nerve head and papillary blood flow in patients with NTG, POAG and in healthy volunteers, as well as to find any possible correlation between selected morphological parameters and papillary blood flow. 21 glaucomatous and 31 normal eyes were diagnosed using HRT and HRF. Statistically significant differences within many morphological parameters like cup area, cup to disc, cup shape measure, rim volume, RFNL thickness, RFNL cross section and neuroretinal rim blood flow appeared. Nevertheless, in glaucoma patients no statistically significant differences between morphology and flow were found. The conclusion is that blood flow impairment within the neuroretinal rim is connected with glaucoma neuropathy development, nevertheless it is affected by other factors.